Formation and Characterization of Aroma Compounds in Camembert Cheese - Bruna Fernanda Damasceno Ramirez; Gustavo Aparecido Martins; Juliano Lemos Bicas; Mário Roberto Maróstica Júnior (Compounds)
The characterization of volatile compounds in cheese is crucial for understanding sensory properties and consumer acceptance. Camembert cheese, a surface-ripened variety, presents a complex aroma profile shaped by biochemical and microbial interactions. Despite advances in analytical methods such as gas chromatography–mass spectrometry (GC–MS) and gas chromatography–olfactometry (GC–O), the metabolic pathways and microbial interactions defining Camembert’s aroma remain incompletely understood. This review explores the synergistic roles of microbial communities, enzymatic activity, and environmental conditions in volatile compound formation. A systematic literature review was conducted using Scopus, Web of Science, and Google Scholar to analyze the classification of volatile compounds, biochemical pathways of aroma formation, and microbial contributions. The findings highlight the essential role of Penicillium camemberti and lactic acid bacteria in aroma modulation, particularly in sulfur compounds, esters, and short-chain fatty acids. Emerging technologies such as solid-phase microextraction (SPME) and metabolomics provide new insights into volatile compound dynamics. Understanding these mechanisms may enhance aroma control in cheese production through microbial engineering and biochemical monitoring. This review underscores the need for integrated approaches to optimize fermentation and ensure sensory standardization, contributing to improved quality and consumer acceptance of Camembert cheese.